Predictors of an adverse course of heart failure with preserved left ventricular ejection fraction in patients with obstructive sleep apnea syndrome - A. T. Teplyakov; A. V. Yakovlev; S. N. Shilov; N. F. Yakovleva; E. N. Berezikova; E. V. Grakova; K. V. Kopeva; S. D. Mayanskaya (Бюллетень сибирской медицины, 2021)
Aim. To study the relationship of obstructive respiratory disorders during sleep with subclinical development of right ventricular dysfunction and pulmonary hypertension, as well as with the risk of an adverse course of chronic heart failure (CHF) with preserved left ventricular ejection fraction (LVEF).Materials and methods. The study included 86 men with moderate and severe forms of obstructive sleep apnea syndrome (OSAS) (with an apnea/hypopnea index (AHI) > 15 per hour). All patients had abdominal obesity and hypertension. Upon inclusion in the study, all patients underwent polysomnography and echocardiography according to the  standard protocol with an additional assessment of the fractional area  change in the right ventricular myocardium (ΔSRV) and the right ventricular  stroke work index (RVSWI). Also, the content of the N-terminal brain natriuretic peptide precursor (NT-proBNP) in the blood serum was  determined by enzyme immunoassay analysis. A six-minute walk test (6MWT) was performed after inclusion in the study and after 12 months of  follow-up. Depending on the course of CHF during the follow-up,  retrospectively, the patients were divided into 2 groups: with an unfavorable (n = 33) and favorable (n = 53) prognosis.Results. A significant relationship between AHI and ΔSRV, RVSWI, NT-proBNP, and 6MWT was revealed. Based on the results of one-way correlation analysis, it was found that ΔSRV (odds ratio (OR) 2.51; 95%  confidence interval (CI) 2.42–3.24; p = 0.0009), NT-proBNP (OR 1.92; 95% CI  1.32–2.78; p = 0.003), and AHI (OR 3.93; 95% CI 2.87–4.11; p = 0.018) were predictors of an adverse course of CHF. In a multivariate analysis, it was found that AHI was an independent predictor of an adverse course of CHF (OR 3.49; 95% CI 2.17–11.73; p = 0.0008), while the addition of NT-proBNP improved risk stratification of an adverse course of CHF (OR 4.66; 95% CI 3.87–13.11; p < 0.0001).Conclusion. The fractional area change in the right ventricular myocardium (ΔSRV) can be considered as a non-invasive marker for determining the  emerging right ventricular dysfunction and predicting adverse cardiovascular events in patients with preserved LVEF and OSAS. Moreover, the combined use of echocardiographic (ΔSRV) and laboratory (NT-proBNP) markers can improve risk stratification of CHF progression.